The effect of different berries in human nutrition - Tordai, E.; Nagy, E.; Stefanovits-Bányai, É.; Papp, J.; Blazovics, A.; Sárdi, É. (International Journal of Horticultural Science, 2007)
The aims of this study were on the one hand to compare of examined compounds according to their importance in nutrition and human-health, and on the other hand we made preexperiments to investigate the relationships among antioxidant capacity and the endogenous substances which contribute the antioxidant status of the plants. The following species were involved in the experiment: raspberry, blackberry, black currant, elderberry and sour cherry. These fruits have potent health-promoting antioxidant power. Glucose, fructose, total phenol, formaldehyde and anthocyanin contents were determined in addition to ferric reducing ability. Our results reflected considerable differences in the measured parameters of the analysed species. In blackberries and elderberries the high antioxidant capacity is coupled with low carbohydrate content. Besides the formerly proven correlations between total phenol content, anthocyanin concentration and antioxidant capacity, these parameters also correlated with the measured formaldehyde concentrations, hereby we can follow the methylation /demethylation status of the plant.